AB0959 The Automated Software-Guided Ultrasound Assessment of Bilateral Common Carotids Intima-Media Thickness for Investigation of Cardiovascular Risk: Comparison between Psoriatic and Rheumatoid Arthritis Patients. (15th July 2016) - Pereira, L.; Soares, G.M.; Dias, M.A.; Ribeiro, P.; Pinheiro, M.M.; Luz, K.
Abstract : Background: Recent studies have shown the relationship between psoriatic and rheumatoid arthritis and subclinical atherosclerosis. Currently, a new automated ultrasound software, based on radio frequency, called RF-QIMT technology, proved to be a useful method for assessing subclinical atherosclerosis with the measurement of the intima-media thickness (IMT) in carotid arteries. Objectives: To compare the carotid IMT in patients with ordinary psoriatic arthritis (PsA) and rheumatoid arthritis (RA) through the RF-QIMT. Methods: Total of 28 patients with APs (n=14) and RA (n=14) were enrolled in this case-control study. Patients with diabetes mellittus, dyslipidemia and previous cardiovascular events excluded. We evaluated the body mass index (BMI) and disease activity, including DAS28 score. The patients underwent a US assessment of the IMT of the posterior wall of common carotids using a My Lab 60 (Esaote SpA, Genoa, Italy) equipped with a 4–13 MHz linear probe adopting an automatic software-guided technique (named RF-QIMT technology). Results: Mean age was 42.5. ±7.7 years and 46, 6± 11.6 years in patients with APs and RA with no statistical difference between the groups (p>0.05). The mean disease duration was 14.1±9, 5 and 6.17±4.4 years (p<0.05) in patients with APs and RA, respectively, with a predominance of men in those with APs (50% vs. 0%) (p<0.05). In addition, there was no statistical difference (p>0.05) between the groups regarding BMI (26.3±5.7 vs. 26.6±4.5 kg/m 2 ) and DAS28 score (3.93±0.7 vs. 2.8±0.63). There was no statistical difference (p>0.05) in relation to the average values of IMT (0.744± 0.244 in APs vs. 0.626 mm ±0.113mm in RA), the standard deviation (SD) of the six average values indicated by the system, were ranging from 12, 7μm to 21μm, respectively. In addition, it was found that 64.3% of the patients with APs and 78.6% of those AR had higher IMT measurement than expected (p>0.05). There was no statistically significant correlation between IMT and the DAS28 score. However, there was a moderate statistically significant correlation (r =0.51; p<0.05) between the higher IMT measurement than expected and the DAS28 score. Conclusions: The results show that patients with APs and AR have high rates of subclinical atherosclerosis, which can be measured by the new adopting an automatic software (called RF-QIMT) of evaluating the IMT, moreover there was correlation and validation with disease activty score. References: Di Geso L, Zardi EM, Afeltra A, Salaffi F, Carotti M, Gutierrez M, Filippucci E et al.Comparison between conventional and automated software-guided ultrasound assessment of bilateral common carotids intima-media thickness in patients with rheumatic diseases. Clin Rheumatol. 2012;31:881–4. Naredo E, Möller I, Gutiérrez M, Bong DA, Cobo T, Corominas H, Corrales A et al. Multi-examiner reliability of automated radio frequency-based ultrasound measurements of common carotid intima-media thickness in rheumatoid arthritis.Rheumatology (Oxford).2011;50:1860–4. Disclosure of Interest: None declared